Hands-on science centers a directory of interactive museums and sites in the United States - Danilov, Victor J.; ebrary, Inc. (Jefferson, N.C. : McFarland, 2010)
"This book contains descriptions of more than 260 museums and sites where the visiting public can touch, handle, and interact with exhibits or objects in both an entertaining and educational way. Each entry includes a brief description of the center's hands-on exhibits, programs, and events, along with contact information, hours, and ticket information"--
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Interactive science museums -- United States -- Directories; Electronic books